Tentative exploration of pharmacodynamic substances: Pharmacological effects, chemical compositions, and multi-components pharmacokinetic characteristics of ESZWD in CHF-HKYd rats - Hong, Li-li; Zhao, Yan; Chen, Wei-dong; Yang, Chen-yu; Li, Guo-zhuan; Wang, Hong-song; Cheng, Xiao-yu (Frontiers in Cardiovascular Medicine, 2022)
The chemical components of Xin'an famous prescription Ershen Zhenwu Decoction (ESZWD) are still unclear. The results showed that ESZWD could significantly reduce left ventricular end diastolic diameter, decrease N-terminal pro-brain natriuretic peptide (NT-proBNP), angiotensinII, aldosterone, reactive oxygen species, and malondialdehyde, increase serum superoxide dismutase, while had no significant effect on inflammatory factors. Ultra-performance liquid chromatography/quadrupole-time-of-flight mass spectrometry (UPLC/Q-TOF-MS) analysis detected 30 prototype components in model rats' serum, mainly including alkaloids, saponins, terpenoids, tanshinones, phenols. UPLC-MS/MS successfully detected the pharmacokinetic parameters of four components, and correlation analysis shows that there are negative correlations between four compounds and serum NT-proBNP. Thirty components of ESZWD may play a therapeutic role in chronic heart failure with heart-kidney Yang deficiency (CHF-HKYd) by improving myocardial injury, reducing oxidative stress levels, and inhibiting activation of the RAAS system in rats. Salsolinol, aconitine, paeoniflorin, and miltrione are equipped with potential characteristics as pharmacodynamic substances for ESZWD in treating CHF-HKYd. Additionally, the constituents of ESZWD in CHF-HKYd rats are different from normal rats, which provided a reference for the selection of subjects for further study.